The Prison Inmate Network Study, United States, 2015 - Kreager, Derek ([Verlag nicht ermittelbar], 2020)
This study advances the understanding of incarceration and its consequences by focusing on prison social systems and their informal network structures. The data for this project are aimed at three research questions: (1) What is the informal social structure within prison? (2) What are the processes through which informal social structure is created and sustained? and (3) What are the consequences of informal social structure and inmates' positions within it for inmate-level and prison-level outcomes? The project takes a network perspective and collected longitudinal data (2 waves) in a single prison unit to reveal the informal network structure and correlate this with inmate health, safety, and rehabilitative outcomes. Network data were collected for "get along with best" and "power and influence" nominations. Behavioral data are combined from multiple sources, including inmate surveys, prison work records, misconduct records, drug tests, visitation lists, and gang classification data.